The blueprint for business objects - Fingar, Peter, 1946- (Managing object technology series, 1996)
Written for software managers, Managing Your Move to Object Technology Guidelines and Strategies for a Smooth Transition clearly defines and illustrates the management implications associated with the transition to object technology. The primary focus of this book is on what OT will do to the corporate culture, than on what it will do for it. Specifically, this book answers the numerous questions surrounding how an organization needs to change to make object technology successful. In frank and concise terms, the author clearly delineates the many difficulties that need to be overcome to successfully manage the transition. In so doing, this book is also extremely useful to those organizations that have already experienced difficulties with the introduction of OT.